Reformulation of Criminal Policy on Sharia Economic Crimes: Integrating Maqāsid Principle into Contemporary Islamic Criminal Law - Zul Khaidir Kadir; Muhammad Reza Zulfikar; Afif Muhni; Fadhil Hayan Mochammad (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
This article examined the reformulation of criminal policy for sharia economic crimes through the perspective of maqāṣid al-sharīʿah, with particular attention to the protection of wealth (ḥifẓ al-māl) as a foundational objective of Islamic law. The study aimed to address the persistent gap between the ethical–normative commitments of Islamic finance and the predominantly positivist criminal justice frameworks applied to economic misconduct in sharia-compliant sectors. A qualitative normative legal method was employed with a critical examination of contemporary statutory regulations. The analysis focused on how criminal liability, sanctions, and procedural mechanisms are currently constructed and the extent to which they align with maqāṣid-based objectives. The findings demonstrated that existing criminal policies tend to treat sharia economic violations as generic financial offenses, thereby failing to account for their distinctive moral, social, and distributive harms. This misalignment weakens deterrence, obscures institutional responsibility, and undermines public trust in sharia economic institutions. The study proposed a maqāṣid-oriented criminal policy framework that redefines economic offenses under the Ta‘zīr paradigm, incorporates corporate criminal liability, and integrates preventive, corrective, and restorative dimensions into enforcement mechanisms. Such a framework strengthens normative coherence between Islamic legal principles and modern criminal justice systems while enhancing the integrity and sustainability of the sharia economy.